AZERBAIJAN’S ENERGY POLICY: ESULTS, PROBLEMS, PROSPECTS - ZHILTSOV, Sergey; SLISOVSKIY, Dmitriy; SHULENINA, Nadezhda; BAZHANOV, Evgeniy (CENTRAL ASIA AND THE CAUCASUS, 2017)
Following the dissolution of the U.S.S.R., Azerbaijan gained the opportunity to shape its energy policy based on its own national interests. In the initial years after attaining independence, Azerbaijan’s energy policy was significantly influenced by internal events related to the power struggle within the Azerbaijani elite. This struggle impeded the expansion of Azerbaijan’s cooperation with Western oil and gas companies, which were increasingly interested in the country's petroleum resources. However, internal political struggles did not alter the country's energy policy priorities, which focused on choosing strategic partners that would facilitate increases in oil and gas production. Ultimately, Azerbaijan opted to collaborate with foreign petroleum companies and strengthen ties with Western states, whose support was crucial for developing petroleum fields and determining oil export routes. Between 1991 and 2017, Azerbaijan's energy policy evolved through several stages. In the early 1990s, the country prioritized oil production, engaging Western petroleum companies drawn by the potential of significant petroleum reserves. With a well-developed infrastructure, experienced personnel, and a rich history of oil production dating back to the 19th century, when Baku was a leading center for oil extraction, Azerbaijan aimed not only to boost production from its Caspian oil fields but also to construct new pipelines for exporting oil. Substantial progress was made in this area, as new pipelines were built with the help of the petroleum business community and Western nations. This surge in oil production enabled Azerbaijan to stabilize its political situation and address social and economic challenges that arose after the Soviet Union's disintegration, which disrupted trade and economic links with other former Soviet republics. In the early 21st century, Azerbaijan’s energy policy underwent a significant transformation. Initially focused on oil, the country shifted its attention toward developing natural gas fields discovered during oil field development. The proven gas reserves and increasing production volumes positioned Baku to plan for expanded exports to international markets. In recent years, Azerbaijan has pursued an energy policy aimed at securing its role as a petroleum exporter to European countries. Cooperation with Turkey has been instrumental in achieving this goal, leading to the implementation of new gas pipeline projects that will enhance Azerbaijan’s natural gas deliveries to external markets. Azerbaijan's energy policy aligns with EU interests, which view Caspian energy resources as a potential alternative to Russian gas exports.